Impact of Interest Income and Joint Income from Commission, Fee, and Discount on Nepalese Commercial Banks’ Net Profit - Dahal, Arjun Kumar (Adhyayan Journal, 2022)
The role of interest income and fee, commission, and discount income on the net profit of Nepalese commercial banks is investigated in this study. It also tries to find short- and long-term relationships between net profit and interest income, as well as income from fees, commissions, and discounts. The panel data of seven commercial banks are studied to look for correlations between dependent and independent variables from fiscal years 2010/11 to 2019/20. Panel unit root testing, Hausman specification test, fixed effect model, Pedroni (Engle-Granger based) co-integration test, Kao residual co-integration test, and Panel –fully modified least squares methods are used. The fixed-effect model can produce efficient outcomes, according to the Hausman test. The fixed-effect model reveals that interest income is significant in explaining commercial banks' net profit. The long-run connections between net profit and its two determinants, such as interest income and income from fee, commission, and discount income, have been discovered using both Pedroni and Kao's co-integration tests. Similarly, the fully modified least square (FMOLS) panel ensures long-term relationships between variables. Both independent factors have a substantial impact on the net profit of Nepalese commercial banks. Commercial banks' net profit is heavily reliant on the interest income from borrowers. The net profit of commercial banks in Nepal increases by 0.466 units for every unit rise in interest income. As a result, authorities must look for alternative ways to boost net profit since issues might arise if the central bank narrows the difference between the depositary and lending interest rates.